Oxygen isotopic fingerprints on the phosphorus cycle within the deep subseafloor biosphere. (1st October 2021) - Zhao, Mingyu; Blake, Ruth E.; Liang, Yuhong; Ruf, Deren Dogru; Jaisi, Deb P.; Chang, Sae Jung; Planavsky, Noah J.
Abstract: Phosphorus (P) is essential for all known forms of life. The oxygen isotopic composition of phosphate can carry a strong imprint from the metabolic processes in Earth's surface environments, including the deep subseafloor biosphere extending to > 1 km beneath the seafloor. Here, we report the 18 O/ 16 O ratios (δ 18 O) of dissolved inorganic phosphate (DIP) to identify different pathways of P cycling in deep-sea sediments sampled up to 200 meters below the seafloor during Ocean Drilling Program (ODP) Leg 201. Our results, along with a diagenetic model, indicate that the δ 18 O of DIP (δ 18 ODIP ) is mainly controlled by three pathways of P cycling at Site 1230: (1) release of DIP by extracellular enzymatic degradation of organic matter (i.e., organophosphate), (2) precipitation of authigenic apatite, (3) enzyme-catalyzed oxygen isotopic exchange between phosphate and water. Our diagenetic model quantitatively deconvolves the rates of the three P cycling pathways. In particular, a shift of δ 18 ODIP towards equilibrium around 140 m below the seafloor corresponds well with a shift in microbial communities, suggesting that δ 18 ODIP has potential as a proxy for microbial activities in the deep subseafloor biosphere. We also find that the rate of oxygen isotopic exchange can be scaled with the rate of organic matter degradation, suggesting microbially controlled oxygen isotopic exchange. Further, the pattern of variation between authigenic phosphate in sediments and DIP in porewaters bolsters the case that authigenic phosphate (authigenic apatite and Fe-bound phosphate) should reflect the oxygen isotopic composition of contemporaneous porewater DIP and thus can be used to track biogeochemical cycling of P.